Interpretation of Student Data in Web-based 21st Century Learning in Junior High School - Dodi Herdiana; Imas Nurmawati; Helmi Hidayati Lestari (APS-TPI, 2025)
Background of Study: Education is an important component in sustaining a nation or state. Preparing superior human resources is one of the country's ideals, including Indonesia, especially with the development of the current era of the Industrial Revolution 4.0 in the 21st century. Education, especially learning, is a fundamental thing that must be strengthened to achieve the desired goals.Aims and Scope of Paper: This study aims to see the extent of student data interpretation related to web-based online learning (web-learning). The prepared data includes students in State Junior High Schools in Garut from grade 7 to grade 9.Methods: The sample in this data is as many as 500 students from various junior high school classes. The results collected by the researcher are data obtained from several questionnaire questions related to online learning (web learning).Result: The findings from the data taken show that approximately of students agree or even strongly agree with online learning. The response of students to learning using web-learning was very positive, with around 52.80% stating that they strongly agreed and agreed. Web learning can increase students towards improving their learning, as shown by the survey results, which is 55.4% of students who answered yes and strongly agree. The response of students to teachers who use web learning is very good, which can be seen from the results of survey number 15 around 61.4%.Conclusion: In conclusion, web-based online learning receives positive responses from students and supports the learning process. The use of web learning helps students adapt to technology-based learning and supports competence development in the 21st century.